CHRONIC NON-COMMUNICABLE DISEASES CAUSED BY ADOLESCENT EATING DISORDERS - Konatar, Ranka; Pelicic, Damir; Maras, Borko; Music, Kenan (Sanamed, 2024)
Decreased satisfaction with physical appearance during adolescence is significantly linked to reduced self-esteem and an increased prevalence of obesity and other chronic non-communicable diseases (NCDs). A major issue in today’s world is the influence of media, which serves as the primary channel through which ideals of physical appearance and attractiveness are transmitted. According to a 2015 study, adolescents spend an average of 17 hours per week watching television. Scientific evidence indicates that an active lifestyle provides health benefits and prevents the occurrence of numerous chronic non-communicable diseases, while improper diet and physical inactivity among adolescents contribute to the development of these diseases. Improper nutrition during adolescence can be a significant risk factor for the development of NCDs. These diseases, including cardiovascular diseases, diabetes, and certain forms of cancer, often have complex causes, but dietary habits can be identified as a common risk factor. Excessive intake of saturated and trans fats, cholesterol, and a high consumption of processed foods are associated with an increased risk of cardiovascular diseases. Improper dietary habits can also contribute to the development of type 2 diabetes and increase cancer risk. Adopting a balanced and nutritionally rich diet, along with regular physical activity, can help prevent and manage these conditions. This review paper is based on a search of the scientific literature published in the last ten years, with a special focus on original research articles published in the last five years from the scientific databases: PubMed, SCOPUS, MEDLINE, and SCI index.
Keywords: public health; prevention; nutrition; risc factors